Estimation of breed composition, breed heterosis and epistatic loss for percent of live spermatozoa in admixed Swiss Fleckvieh bulls - Khayatzadeh, Negar; Mèszáros, Gabor; Utsunomiya, Yuri Tani [UNESP]; Schmitz-Hsu, Fritz; Gredler, Birgit; Schnyder, Urs; Ferenčaković, Maja; Curik, Ino; Sölkner, Johann (My University, 2017)
The objective of this study was to estimate non-additive genetic effects of heterosis and epistatic loss on percent of live spermatozoa in admixed Swiss Fleckvieh bulls, a composite of Simmental and Holstein Friesian cattle. Heterosis is the additional gain in productivity or fitness of crossbred progeny over the mid purebred parents mean which arises from intra-locus gene interaction. Epistatic effects generally reduce productivity or fitness due to lack of gene interactions of genes from different breeds, which is called epistatic loss. Bovine SNP chip data of were used to predict locus specific breed origin of alleles along the autosomes of 815 admixed bulls as well as 147 Holstein Friesian and 207 Simmental bulls representing the parental breeds. The breed proportions for admxied bulls based on 32,899 SNP were used to calculate breed heterozygosity and epistatic loss, considering additive by additive effects for 1,000,000 random pairs of loci. The average Holstein Friesian ancestry in admixed bulls was estimated to be 0.82. Results of fitting different linear mixed models showed that including breed heterozygosity and epistatic loss improved the model fitness (ΔAIC > 3). The heterosis effect and epistatic loss were estimated 2.5(±1.39) % and -0.65(±1.68) % of live spermatozoa, respectively. High correlation (0.97) between breed heterozygosity and epistatic loss values indicate strong confounding of these effects in the model, indicating that it is not possible to properly separate these effects.
Keywords: Admixture; Breed composition; Epistatic loss; Heterosis; Live spermatozoa; Swiss Fleckvieh